Cloning and expression of OdTx12, a β excitatory toxin from Odontobuthus doriae, in Escherichia coli and evaluation of its bioactivity in Locusta migratoria. (August 2020) - Khoshdel Nezamiha, Farahnaz; Imani, Sohrab; Shahbazzadeh, Delavar; Tirgari, Syavash; Arabi Mianroodi, Reza
Abstract: The venom of Odontobuthus doriae contains several peptide toxins that interfere with the sodium channel function of cell membranes, some of which specifically act on the insect's sodium channel without affecting mammalian cells. In this study sodium channel toxins of Odontobuthus doriae were aligned to other closely related toxins by BLAST and ClustalW servers. Among these toxins, NaTx12 (OdTx12) showed more than 90% similarity to the most known beta excitatory toxin, AaHIT1; furthermore, our modeling studies confirmed high tertiary structure similarity of these proteins. OdTx12 was cloned and expressed in E.coli, using pET26-b and pET28-a expression vectors. Tris-tricine SDS-PAGE and Western blot analysis showed OdTx12 expression by pET28-a, only. After purification, bioactivity of the purified protein was analyzed by injection and oral administration to Locusta migratoria larvae, and toxicity to mammals was tested on mice. Injection of OdTx12 resulted in the killing of larvae with LD50 of 0.4 and 0.2 after 48 and 72 h respectively, but oral administration of OdTx12 had no significant effect on Locusta migratoria, nor did the injection to mice show any signs of toxicity. These results showed that OdTx12, as a novel β excitatory toxin can be considered as a candidate for insect control purposes. Highlights: With the advent of biological control methods and the use of synthetic pesticides has been decreased. Scorpion venoms contain a large number of neurotoxic polypeptides. OdTx12 shows more than 90% similarity to the most known beta excitatory toxin, AaHIT1. β excitatory toxins can be considered as candidates for insect control purposes.